Energy research in East Africa: A bibliometric analysis - Rady, Mohammed; Alasow, Ahmed Abdiaziz; Hersi, Abdifatah Ahmed (Taylor & Francis Ltd, 2025)
East Africa faces significant energy challenges due to the growing demand for sustainable power sources. Although the past decades have revealed an increase in global energy research, a comprehensive analysis of energy research is lacking in East Africa. To this end, we conducted a bibliometric analysis of energy research in East Africa over the past 25 years using the Scopus database, examining 905 publications from 412 journals. The results revealed a significant increase in energy research, with an annual growth rate of 10.07% in publications. The top contributing institution is Addis Ababa University (Ethiopia), accounting for 41 studies, followed by Makerere University (Uganda) and the University of Rwanda with 29 and 26 publications, respectively. The keyword analysis revealed a strong regional emphasis on East African countries, particularly Ethiopia, Kenya, and Tanzania, with a significant focus on energy policy, economic analysis, and technological aspects including solar and wind power. International collaboration patterns showed the UK, USA, and Ethiopia as leading contributors, with dense research networks connecting East African institutions to partners in Europe, Asia, and North America. The Engineering and Physical Sciences Research Council and World Bank Group were the top funding sources, demonstrating significant international investment in the region’s energy research. While Ethiopia and Kenya contributed the most to energy research, Somalia and South Sudan had a lower role in energy research in the region. The findings highlight the need for more balanced energy research efforts across the region by identifying regions that require further attention.